The impact of Covid-19 on global value chains - Heli Simola (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
The Covid-19 pandemic has hit international trade hard, creating concerns of serious disruptions to global value chains (GVCs). This paper provides a preliminary analysis on the development of GVC trade during the current crisis with a focus on the internal and external trade of the EU. The potential consequences of the pandemic and other key factors for GVCs are discussed on the basis of a review of recent literature. We find that trade overall has been hit hard by the pandemic, but not GVC trade in particular. The sector of transport equipment makes a notable exception. Our analysis suggests that the Covid-19 crisis will not necessarily lead to a major restructuring of GVCs, but could fortify several trends shaping GVC development. While several factors limit future expansion of GVCs, the requisite complexity and high restructuring costs of existing GVCs make it unlikely that they will be dismantled anytime soon.
urn:nbn:fi:bof-202101141046
Keywords: 330; Global value chains; International trade; Covid-19